THE ROLE OF JOB SATISFACTION IN ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON IMPROVING PERFORMANCE - Trisya Rifaningrum Sholikhah; Suyoto Suyoto Suyoto; Mahjudin Mahjudin Mahjudin; Achmad Daeng GS; Fery Adhy Permana (Universitas 17 Agustus 1945 Surabaya, 2021)
Service companies in the health sector are closely related to performance appraisals to solve health problems in various circles of society. This study aims to determine the role of job satisfaction in organizational culture and work motivation on employee performance. This study uses a descriptive quantitative method with respondents all employees of PT. Main eye clinic as research sample. The data analysis technique used path analysis with 30 respondents. The results showed that organizational culture has an effect on employee performance, work motivation has an effect on employee performance, organizational culture has an effect on job satisfaction, job motivation has an effect on job satisfaction, job satisfaction on employee performance, organizational culture affects employee performance through job satisfaction as a mediation, motivation. work affects employee performance through job satisfaction as a mediation.